Images of Death in Animated Films Aimed at Children - an Educational Dimension - Maciaszek, Piotr (INSTED: Interdisciplinary Studies in Education & Society, 2024)
The aim of this article is to analyse the way death and the process of dying are portrayed in animated films aimed at children and to show their educational potential. The article reflects on the diverse images of death present in three films: Coco (2017, Lee Unkrich), Onward (2020, Dan Scanlon) and Soul (2020, Pete Docter), and their impact on young audiences’ perception of death. These films present death not as a final end but as a natural part of life, often taming the subject through symbolic and metaphorical elements. The author draws attention to the role of films as educational tools that can help children deal with difficult emotions related to the process of dying and death. The article also outlines the potential of using films as educational tools, including in tanatoeducation. The author emphasises that although the films analysed do not offer clear-cut answers regarding death, they can provide an important starting point for reflection on its role in the human experience.